Dynamic investigation and alleviative measures for the skidding phenomenon of lubricated rolling bearing under light load. (1st February 2023) - Liu, Yuqing; Chen, Zaigang; Li, Yifan; Zhai, Wanming
Abstract: The skidding phenomenon occurs during the operation of rolling bearing under the light load owing to the design error, which will intensify the surface damage and lead to noise and abnormal vibration. In this study, a skidding dynamics model of lubricated rolling bearing is established considering the interactions between the roller and races, as well as the cage. The effect of lubricant on the dynamic characteristics of the rolling bearing is characterized as the lubricating oil stiffness, central film thickness, time-varying friction coefficient between the roller and race, passing flow resistances of rollers, and resistance torques. In addition, the nonlinear contact and structure deformations of rollers are formulated. For mitigating the skidding phenomenon of the roller under light load, the effect of roller number, inside radius of the hollow roller, density and viscosity of the lubricant, interference fit, and radial load are analyzed. The results indicate that the skidding phenomenon of the roller is induced by the lesser tangential roller-race friction forces and larger passing flow resistances of rollers. It is helpful to intensify the interactions at the roller-race interface or/and decrease the running resistance by reducing the roller number, decreasing the lubricant density, or choosing the correct viscosity of the lubricant. Besides, the effect of interference fit and increasing radial load is significant on the premise of not changing the design parameters of the rolling bearing.